INFLUENCE OF ORIGIN AND SIZE OF POTATO PLANTING MATERIAL ON MORPHOLOGICAL CHARACTERISTICS OF SEED TUBERS - Poštić, Dobrivoj; Štrbanović, Ratibor; Broćić, Zoran; Popović, Tatjana; Marković, Sanja; Jelušić, Aleksandra; Stanisavljević, Rade (Journal on Processing and Energy in Agriculture, 2021)
The aim of this study was to determine the influence of the origin and size of planting material on the mophological characteristics of seed tubers three potato cultivars. The objects of research were three varieties of potatoes: two middle early (Aladdin and Newton) and middle late (Desiree). The analysis of the morphological characteristics tuber showed highly significant (р
Keywords: potato tuber, planting material, sprout